Cost-effectiveness Analysis of Rivaroxaban versus Acenocoumarol in the Prevention of Stroke in Patients with Non-valvular Atrial Fibrillation in Spain - Carlos Rubio-Terrés; Ruth Graefenhain de Codes; Darío Rubio-Rodríguez; Thomas Evers; Santiago Grau Cerrato (Journal of Health Economics and Outcomes Research)
# Objective The aim of this study was to evaluate, from the Spanish National Health System perspective, the cost-effectiveness of rivaroxaban (20 mg/day) versus use of acenocoumarol (5 mg/day) for the treatment of patients with non-valvular atrial fibrillation (NVAF) at moderate to high risk for stroke.